The effect of acoustic mode on time-resolved temperature measurements in a Rijke-tube pulse combustor - McQuay, M. Q.; Dubey, R. K.; Carvalho, J. A. (Elsevier B.V., 2000)
Radial profiles are reported of average and rms temperature in a propane flame for the first, second, and third acoustic modes at four different axial positions above the burner in a Rijke-tube combustor. Selected plots of the power spectral density (PSD) of temperature fluctuations are also reported. These radial profiles are then compared to similar ones made in the same flame, but in the absence of the acoustic field. Visual observations and photographs of the flame showed a remarkable change in flame height and structure with the onset of acoustic oscillations. This reduction in flame length, caused by the enhanced mixing due to the acoustic velocity fluctuations, gave rise to higher and lower average and rms temperatures near or well above the burner, respectively. In general, the PSD plots had a broad frequency content. The general trend was a decrease in magnitude with an increase in frequency. All cases presented broad-band peaks at around 5 Hz related to the flame flickering phenomenon. Preferred frequencies were observed in the oscillating PSD plots related to the fundamental frequency as well as subharmonics in the tube. (C) 2000 Elsevier B.V. Ltd. All rights reserved.
Keywords: thermal structure; thermocouple probes; Rijke-tubes